Developing a Virtual Escape Room Game: Existing Challenges and How to Overcome Them - Araújo, Calíope Corrêa de; Melo, Jaqueline Ferreira Holanda de; Teixeira, João Marcelo Xavier Natário; Peres, Fabiana Frata Furlan (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2023)
This paper presents the challenges faced during the conception and development of a virtual reality game, of the Escape Room type, for simulation on the Meta Quest 2 mobile device. Based on the experience obtained, some important insights are provided, which are necessary to overcome the challenges faced and to promote a greater immersion of the player in the virtual environment. Related works demonstrate the importance of evaluating and continuing the studies presented, seeking to identify and promote significant purposes for virtual games, and promoting virtual reality teaching and learning based on the creation of proposals dedicated to immersive devices in a 3D virtual environment.